Handbook of plant-based fermented food and beverage technology. - Hui, Y. H. (Yiu H.), 1940-2015 (Boca Raton : CRC, 2012)
Progress in the biological and microbiological sciences involved in the manufacture of fermented foods has led to commercialization and heightened interest among scientists and food processors. This volume is an up-to-date reference exploring the history, microorganisms, quality assurance, and manufacture of fermented food products derived from plant sources. The book begins by describing fermented food flavors, manufacturing, and biopreservation. It then supplies a detailed exploration of a range of products derived from soy, fruit, vegetables, and cereals. It also explores various specialty products, including balsamic vinegar and coconut milk, and examines ingredients such as proteolytic bacteria, enzymes, and probiotics.